Cross metathesis of unsaturated epoxides for the synthesis of polyfunctional building blocks - Abderrezak, Meriem K (Beilstein J Org Chem, 2015)
The cross metathesis of 1,2-epoxy-5-hexene (1) with methyl acrylate and acrylonitrile was investigated as an entry to the synthesis of polyfunctional compounds. The resulting cross metathesis products were hydrogenated in a tandem fashion employing the residual ruthenium from the metathesis step as the hydrogenation catalyst. Interestingly, the epoxide ring remained unreactive toward this hydrogenation method. The saturated compound resulting from the cross metathesis of 1 with methyl acrylate was transformed by means of nucleophilic ring-opening of the epoxide to furnish a diol, an alkoxy alcohol and an amino alcohol in high yields.